Pharmacokinetics of Edoxaban 15 mg in Very Elderly Patients with Nonvalvular Atrial Fibrillation: A Subanalysis of the ELDERCARE-AF Study - Yamashita, Takeshi; Igawa, Yoshiyuki; Fukuzawa, Masayuki; Hayashi, Takuya; Hennig, Stefanie; Okumura, Ken (Thrombosis and Haemostasis, 2024)
Background We evaluated the pharmacokinetics (PK) of low-dose (15 mg) edoxaban in very elderly patients (≥80 years) with nonvalvular atrial fibrillation (NVAF) and high bleeding risk.Methods This subanalysis of the phase 3, randomized, double-blind, placebo-controlled, multicenter ELDERCARE-AF study evaluated edoxaban plasma concentrations and compared them with the Japanese population of the ENGAGE AF-TIMI 48 and Japanese severe renal impairment (SRI) studies.Results The PK analysis population included 451 patients, 53.8% of whom concomitantly used antiplatelet drugs, 41.0% had SRI, and 38.0% had low body weight. Edoxaban plasma concentrations at trough and 1 to 3 hours post-dose in ELDERCARE-AF were 17.3 ± 13.9 (n = 427) and 93.3 ± 57.8 ng/mL (n = 447), respectively. These values were slightly higher than the 15 mg group in ENGAGE AF-TIMI 48 (n = 79; 12.4 ± 12.1 and n = 115; 78.7 ± 45.0 ng/mL, respectively), lower than the ENGAGE AF-TIMI 48 high-dose reduced to 30 mg group (n = 83; 25.1 ± 36.6 and n = 111; 150 ± 91.6 ng/mL, respectively), but similar to the Japanese SRI study (n = 39; 18.4 ± 11.2 and n = 40; 96.8 ± 48.3 ng/mL, respectively). ELDERCARE-AF patients with SRI and low body weight (≤45 kg) had higher concentrations than those without, and those taking antiplatelet drugs had lower concentrations than those who were not.Conclusion PK data support edoxaban 15 mg once daily for very elderly NVAF patients with high bleeding risk, with caution for patients with SRI and/or low body weight.
Keywords: edoxaban; nonvalvular atrial fibrillation; elderly; pharmacokinetics